Comparing the Effects of Aerobic Exercise and Wet Cupping on the Serum Concentration of Immunoglobulins in the Immune System of Older Women - Amir Delshad; Narges Chamani (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives With aging, cellular changes cause a decrease in the function of the immune system in the elderly. Aging is associated with impaired local inflammatory response necessary to control pathogens. Regular exercise is a healthy lifestyle behavior that can reduce the immune system-related health problems in the elderly. This study aims to compare the effect of six weeks of aerobic exercise and wet cupping on immunoglobulins (IgG, IgE and IgA) in older women. Methods & Materials In this quasi-experimental study, 40 inactive older women aged 55-65 years participated. Based on Vo2max and BMI, they were randomly divided into four groups: Aerobic exercise (n=10), one time cupping (n=10), two times cupping (n=10), and control (n=10). Aerobic exercises with an intensity of 60-75% of heart rate reserve was performed three times a week for six weeks. The wet cupping was done once in the third week of the study and twice in the second and fifth weeks of the study. Before (pre-test) and 48 hours after the end of the last training session (post-test), blood sampling was done to measure IgG, IgE and IgA levels. The analysis of covariance was used for within-group comparison and paired t-test was used to compare pre-test and post-test scores in SPSS software version 25. The significance level was set at 0.05. Results After six weeks of aerobic exercise and wet cupping, the serum levels of IgG (P=0.003), IgE (P=0.013) and IgA (P=0.026) decreased significantly compared to the control group. The decreases were higher in the aerobic group. The results of paired t-test showed a significant decrease in IgG, IgE and IgA levels after interventions in the aerobic and two times cupping groups, compared to their pre-test levels. Conclusion It seems that aerobic exercise and wet cupping can affect the immune system of older women. These interventions can be used to prevent diseases caused by aging and improve the function of immunoglobulins in older women.